NEPS-Metafile.do - A do-file to generate a metafile on the Scientific Use Files of the NEPS: Application of the do-file and documentation of the resulting metafile including syntax examples on the use of the metafile - Klaudia Erhardt (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2023)
NEPS-Metafile.do is a Stata program that generates a Stata file containing information on every variable of the NEPS Scientific Use Files. This paper documents the indicators and characteristics that are extracted from the source files and gives detailed instructions on how to apply NEPSMetafile.do. Using the resulting metafile is demonstrated by extensive syntax examples. The complete syntax of NEPS-Metafile.do is included in the appendix and can also be downloaded (see link below).
https://doi.org/10.7802/2606
Keywords: 300; NEPS Scientific Use Files; metafile; data management utility; Stata syntax